ELF Nonlinear Noise Processing Experimental Measurements, Part 2 - Synoptic Sample of Diurnal and Seasonal Noise Variation in Norway - Davis, John R.; Meyers, William D. (1976)
Using a suitable nonlinearity in the input stage of an extremely low frequency receiver can improve received signal-to-noise ratio S/N by whitening the nongaussian atmospheric noise at these frequencies. Previous studies indicate that performance of simple clippers, carefully adjusted on the basis of the raw noise amplitude statistics, is very nearly equal to that of the optimum clipper. A collection of ELF noise data for all seasons and nearly all times of day has been acquired at a receiving site in the auroral zone near Tromso, Norway. These data have been used to evaluate the improvement in S/N that can be expected from simple clipping under a variety of noise and propagation conditions. A regular diurnal variation in effective (processed) noise level is observed under quiet conditions. Under both quiet and noisy conditions little performance difference is observed among processing channels with clipping levels as far apart as 6 to 18 dB, in the vicinity of the optimum clipping level. The nonlinear processing method described in this report provides at least 10 dB of S/N improvement over the performance obtained without suitable processing.